2010
DOI: 10.1038/emboj.2010.127
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin tunes T-cell activation by controlling Dlg1 and microtubule positioning at the immunological synapse

Abstract: T-cell receptor (TCR) signalling is triggered and tuned at immunological synapses by the generation of signalling complexes that associate into dynamic microclusters. Microcluster movement is necessary to tune TCR signalling, but the molecular mechanism involved remains poorly known. We show here that the membrane-microfilament linker ezrin has an important function in microcluster dynamics and in TCR signalling through its ability to set the microtubule network organization at the immunological synapse. Impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(176 citation statements)
references
References 53 publications
7
165
1
3
Order By: Relevance
“…This anchoring prevents IL-7R diffusion and stabilizes the recruitment of other receptors, such as integrin (10,26). Tubulin anchors to actin microfilaments, potentially through ezrin at its minusend (27), and polymerizes to form a microtubule that grows by its plus-end (28,29), crosses the cytoplasm, and reaches the nucleus less than 2 min after the addition of IL-7 (Figs. 3g and 7c).…”
Section: Sted Microscopy Analysis Of Il-7-induced Membrane Microdomaimentioning
confidence: 99%
“…This anchoring prevents IL-7R diffusion and stabilizes the recruitment of other receptors, such as integrin (10,26). Tubulin anchors to actin microfilaments, potentially through ezrin at its minusend (27), and polymerizes to form a microtubule that grows by its plus-end (28,29), crosses the cytoplasm, and reaches the nucleus less than 2 min after the addition of IL-7 (Figs. 3g and 7c).…”
Section: Sted Microscopy Analysis Of Il-7-induced Membrane Microdomaimentioning
confidence: 99%
“…Finally, other factors may also contribute to the interaction between actin and MTs to coordinate force generation (e.g., perturbation of ezrin-disrupted immune synapse shape) potentially by affecting the link between cortical actin and the MT network (67).…”
Section: Discussionmentioning
confidence: 99%
“…105 Moreover, ERM proteins also play a role in cAMP-mediated T-cell repression by regulating PKA signaling. 106,107 In addition to Rho, PKCa and PKCh, recent studies have identified several GCK family members including MST1, MST4, NCK-interacting kinase (NIK) and lymphocyte-oriented kinase (LOK) as upstream kinases that can directly phosphorylate ERM.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%